A dispersant for enriching regenerative lithium iron phosphate powder magnetic substance, a preparation method and application thereof

CN122898282APending Publication Date: 2026-10-13WUHU ETC BATTERY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610917934.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这不仅造成测试样品损失,使得测试结果偏低,产生较大的测试误差,更重要的是,粘附的粉料会物理阻隔磁性物质与磁棒的接触,导致具有磁性的杂质无法被有效吸附,严重干扰检测结果的真实性

Benefits of technology

[0030]1、本发明通过引入NMP作为PVDF的良好溶剂,能够溶解或溶胀修复型磷酸铁锂中残留的PVDF粘接相,破坏其粘性结构,从根本上消除了粉料粘附磁棒的根源;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898282A_ABST
    Figure CN122898282A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion battery repair detection, and discloses a dispersant for enriching magnetic substances of regenerated lithium iron phosphate powder, a preparation method and application thereof. The dispersant is prepared by mixing N-methyl pyrrolidone, ethanol, organic silicon nonionic surfactant and water. By constructing a composite dispersion system, the destruction of the PVDF bonding network in the repaired lithium iron phosphate powder and the effective inhibition of particle agglomeration are realized. The dispersant has the performance advantages of reducing the adhesion of the powder on the surface of the magnetic bar and improving the enrichment efficiency of the magnetic substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery repair and testing technology, specifically relating to a dispersant for enriching magnetic materials in regenerated lithium iron phosphate powder, its preparation method, and its application. Background Technology

[0002] With the wave of lithium-ion battery retirements, the repair and reuse of lithium iron phosphate batteries has become a hot topic in the industry. The lithium iron phosphate powder obtained from repair typically needs to be reused in battery manufacturing. However, magnetic materials introduced during the repair process (such as elemental or oxide particles of iron, chromium, and nickel) can severely affect the electrochemical performance and safety of the recycled materials. Therefore, accurate enrichment detection of magnetic material content is crucial.

[0003] Traditional enrichment methods typically use water as a dispersant to disperse lithium iron phosphate powder, which is then inserted into a magnetic rod for the enrichment and adsorption of magnetic materials. This method is effective for cathode scraps or pure powder without binders. However, for recycled lithium iron phosphate, whose sources are complex, it often contains residual polyvinylidene fluoride (PVDF) binder. When water is used as a dispersant, PVDF, being insoluble in water and possessing a certain viscosity, causes lithium iron phosphate powder to agglomerate and adhere extensively to the surface of the magnetic rod. This not only results in sample loss and lower test results, leading to significant testing errors, but more importantly, the adhered powder physically blocks the contact between magnetic materials and the magnetic rod, preventing the effective adsorption of magnetic impurities and severely interfering with the accuracy of the test results.

[0004] Therefore, it is necessary to develop a novel pretreatment dispersant to solve the problem of magnetic rod adhesion caused by residual PVDF in regenerated lithium iron phosphate in the existing technology. Summary of the Invention

[0005] The purpose of this invention is to provide a dispersant for enriching magnetic materials in regenerated lithium iron phosphate powder and its preparation method. A composite dispersion system is formed by N-methylpyrrolidone, ethanol, organosilicon nonionic surfactant and water to effectively disperse agglomerated particles in regenerated lithium iron phosphate powder and reduce the adhesion of powder to the surface of magnetic rods.

[0006] The present invention also aims to provide an application of a dispersant for enriching magnetic substances in regenerated lithium iron phosphate powder, which is used to enrich magnetic impurities in lithium iron phosphate powder and facilitates detection.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] This invention provides a dispersant for enriching magnetic materials in regenerated lithium iron phosphate powder, wherein the dispersant is prepared from the following raw materials by mass percentage:

[0009] N-methylpyrrolidone 20%-40%;

[0010] 10%-20% ethanol;

[0011] 5%-10% organosilicon nonionic surfactant;

[0012] Water content: 30%-65%.

[0013] According to a specific embodiment of the present invention, preferably, the dispersant is prepared from raw materials comprising the following components by mass percentage:

[0014] N-methylpyrrolidone 30%-40%;

[0015] Ethanol 15%-20%;

[0016] Organosilicon nonionic surfactants: 7.5%-10%;

[0017] Water content: 30%-45%.

[0018] The type of the organosilicon nonionic surfactant is FY-4903.

[0019] This invention provides a method for preparing a dispersant for enriching magnetic materials in the above-mentioned recycled lithium iron phosphate powder, the preparation method comprising the following steps:

[0020] N-methylpyrrolidone, water, ethanol, and an organosilicon nonionic surfactant are mixed to obtain the magnetic material dispersant for the regenerated lithium iron phosphate powder.

[0021] This invention provides the application of the above-mentioned dispersant for enriching magnetic materials in regenerated lithium iron phosphate powder in the enrichment of magnetic materials in regenerated lithium iron phosphate powder.

[0022] A method for enriching magnetic materials in regenerated lithium iron phosphate powder, the method comprising the following steps:

[0023] 1) The recycled lithium iron phosphate powder and the dispersant as described in claim 1 are placed in a container and mixed to obtain a pretreated product;

[0024] 2) Place the magnetic rod in the stirring device, add the pretreatment material to the stirring device and stir. After completion, clean and collect the material adsorbed on the magnetic rod to complete the regeneration and repair of the enrichment of magnetic materials in the lithium iron phosphate powder.

[0025] In step 1), the mass ratio of lithium iron phosphate powder to dispersant is 1:2-2.5.

[0026] In step 2), the magnetic rod is a Teflon magnetic rod, and the magnetic induction intensity of the magnetic rod is 5500-6000GS.

[0027] According to a specific embodiment of the present invention, preferably, in step 2), the stirring device is a ball mill.

[0028] In step 2), the stirring speed is 115-125 rpm and the stirring time is 30 min.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. This invention introduces NMP as a good solvent for PVDF, which can dissolve or swell the residual PVDF binder phase in the repairable lithium iron phosphate, destroy its adhesive structure, and fundamentally eliminate the root cause of powder adhesion to the magnetic rod.

[0031] 2. The addition of ethanol reduces the surface tension of the mixture and, in conjunction with the organosilicon nonionic surfactant, greatly improves the dispersibility of the powder in the solvent, prevents particle agglomeration, and allows the magnetic material to be fully exposed.

[0032] 3. By preventing powder adhesion and agglomeration, the surface of the magnetic rod remains clean, allowing it to directly and fully contact and effectively adsorb magnetic substances in the suspension. This makes the test results closer to the true values, greatly improving the accuracy and repeatability of the detection.

[0033] 4. The raw materials used in this dispersant formulation are all commonly used industrial solvents, which are widely available and have low cost, making them suitable for industrial application. Attached Figure Description

[0034] Figure 1 An image showing the enrichment effect of using the product described in Example 1 as a dispersant in Application Example 1;

[0035] Figure 2 An image showing the enrichment effect of using the product described in Example 2 as a dispersant in Application Example 1;

[0036] Figure 3 An image showing the enrichment effect of using the product described in Comparative Example 1 as a dispersant in Application Example 1;

[0037] Figure 4 The enrichment effect diagram shows the product described in Comparative Example 2 used as a dispersant in Application Example 1;

[0038] Figure 5 The enrichment effect diagram shows the product described in Comparative Example 3 used as a dispersant in Application Example 1.

[0039] Figure 6An image showing the enrichment effect of using the product described in Comparative Example 4 as a dispersant in Application Example 1;

[0040] Figure 7 This is a graph showing the enrichment effect of using the product described in Comparative Example 5 as a dispersant in Application Example 1. Detailed Implementation

[0041] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0043] Example 1

[0044] A dispersant for enriching magnetic materials in recycled lithium iron phosphate powder, said dispersant being prepared from raw materials comprising the following components by mass percentage:

[0045] N-methylpyrrolidone 20%;

[0046] 10% ethanol;

[0047] 5% organosilicon nonionic surfactant;

[0048] Water content: 65%.

[0049] A method for preparing a dispersant for enriching magnetic materials in recycled lithium iron phosphate powder specifically includes the following steps:

[0050] N-methylpyrrolidone, water, ethanol, and an organosilicon nonionic surfactant are mixed to obtain a dispersant for enriching magnetic materials in the regenerated lithium iron phosphate powder.

[0051] Example 2

[0052] A dispersant for enriching magnetic materials in recycled lithium iron phosphate powder, said dispersant being prepared from raw materials comprising the following components by mass percentage:

[0053] N-methylpyrrolidone 40%;

[0054] 20% ethanol;

[0055] 10% organosilicon nonionic surfactant;

[0056] Water 30%.

[0057] A method for preparing a dispersant for enriching magnetic materials in recycled lithium iron phosphate powder specifically includes the following steps:

[0058] The preparation method in this embodiment is the same as that described in Example 1.

[0059] Comparative Example 1

[0060] The substance used in this comparative example is water.

[0061] Comparative Example 2

[0062] The substance used in this comparative example is N-methylpyrrolidone.

[0063] Comparative Example 3

[0064] The substance used in this comparative example is ethanol.

[0065] Comparative Example 4

[0066] A dispersant, said dispersant being prepared from raw materials comprising the following components by mass percentage:

[0067] N-methylpyrrolidone 20%;

[0068] 10% ethanol;

[0069] Water 70%.

[0070] A method for preparing a dispersant specifically includes the following steps:

[0071] The dispersant is obtained by mixing N-methylpyrrolidone, ethanol and water.

[0072] Comparative Example 5

[0073] A dispersant, said dispersant being prepared from raw materials comprising the following components by mass percentage:

[0074] N-methylpyrrolidone 20%;

[0075] 5% organosilicon nonionic surfactant;

[0076] Water content: 75%.

[0077] A method for preparing a dispersant specifically includes the following steps:

[0078] The dispersant is obtained by mixing N-methylpyrrolidone, an organosilicon nonionic surfactant, and water.

[0079] Application Example 1

[0080] A method for enriching magnetic materials in regenerated lithium iron phosphate powder specifically includes the following steps:

[0081] 1) Mix 150g of regenerated lithium iron phosphate powder with 300g of the dispersant described in each example and comparative example, and stir until homogeneous to obtain the pretreated material;

[0082] 2) Place the 6000GS Teflon magnetic rod in the pretreatment material, put it in the center of the ball mill, set the speed to 120rpm, and stir for 30min. After completion, wash the magnetic rod adsorbed material with ethanol 3 times and collect the magnetic material enrichment in the regenerated lithium iron phosphate powder.

[0083] Test Example 1

[0084] Magnetic material testing:

[0085] In step 2) of Application Example 1, 10 mL of aqua regia was added to the collected material after cleaning with the magnetic rod adsorbed by the magnetic rod. Water was then added to bring the volume to 250 mL. The content of magnetic substances in each example and comparative example was tested using ICP. Magnetic impurities in the table refer to elemental Fe, Ni, Zn, or Cr or their oxides. The ferrous phosphide content in the table is first determined by ICP measurement of lithium, iron, and phosphorus content. The lithium iron phosphate content is then determined by the lithium content. After deducting the iron and phosphorus contributions from lithium iron phosphate, the remaining phosphorus is converted to ferrous phosphide. The remaining iron is counted as elemental iron or iron oxides among the magnetic impurities. The test results are shown in Table 1 below.

[0086] Table 1 Test data of magnetic materials

[0087]

[0088] Combination Figures 1-7 As can be seen from Table 1 above, in Examples 1 and 2, ferrous phosphide and magnetic materials in lithium iron phosphate powder were uniformly adsorbed only at the position where the magnetic strength was strongest on the Teflon magnetic rod. At the same time, the content of ferrous phosphide and magnetic impurities was the highest in the magnetic material test data.

[0089] In Comparative Example 1, water was used entirely as a dispersant, resulting in a large amount of powder adhering to the magnetic rod. This prevented the magnetic materials in the powder from being effectively adsorbed, and the test results for the content of iron phosphide, magnetic metals, and their oxides were the lowest.

[0090] In Comparative Example 2, NMP was used as the dispersant. A small amount of powder still adhered to the magnetic rod, but the magnetic material in the powder was not completely and effectively adsorbed, resulting in a lower magnetic material content than in Examples 1 and 2.

[0091] In Comparative Example 3, ethanol was used entirely as a dispersant, resulting in a large amount of powder adhering to the magnetic rod. This prevented the magnetic material in the powder from being effectively adsorbed, leading to a lower magnetic material content test result compared to Examples 1 and 2.

[0092] In Comparative Example 4, the addition of the organosilicon nonionic surfactant was removed, and a small amount of powder adhered to the magnetic rod. However, the magnetic material in the powder was not completely and effectively adsorbed, resulting in a lower magnetic material content than in Examples 1 and 2.

[0093] In Comparative Example 5, the addition of ethanol was removed, and there was almost no powder adhering to the magnetic rod. However, the test results showed that the content of magnetic material was lower than that in Examples 1 and 2, indicating that the powder was not effectively dispersed and the dispersion effect was poor, resulting in the magnetic material not being completely adsorbed.

[0094] In summary, the dispersant provided by the invention can effectively solve the problem of magnetic rod adhesion, enabling magnetic materials to be effectively adsorbed and collected, resulting in test results that are closer to the true values ​​and significantly improved accuracy.

[0095] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0096] The above description of the embodiments is intended to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A dispersant for enriching magnetic materials in recycled lithium iron phosphate powder, characterized in that, The dispersant is prepared from the following raw materials by mass percentage: N-methylpyrrolidone 20%-40%; 10%-20% ethanol; 5%-10% organosilicon nonionic surfactant; Water content: 30%-65%.

2. The dispersant according to claim 1, characterized in that, The dispersant is prepared from the following raw materials by mass percentage: N-methylpyrrolidone 30%-40%; Ethanol 15%-20%; Organosilicon nonionic surfactants: 7.5%-10%; Water content: 30%-45%.

3. The dispersant according to claim 1 or 2, characterized in that, The type of the organosilicon nonionic surfactant is FY-4903.

4. A method for preparing a dispersant as described in any one of claims 1-3, characterized in that, The preparation method includes the following steps: N-methylpyrrolidone, water, ethanol, and an organosilicon nonionic surfactant are mixed to obtain the magnetic material dispersant for the regenerated lithium iron phosphate powder.

5. The application of the dispersant as described in any one of claims 1-3 in the enrichment of magnetic materials in regenerated lithium iron phosphate powder.

6. A method for enriching magnetic materials in regenerated lithium iron phosphate powder, characterized in that, The method includes the following steps: 1) The recycled lithium iron phosphate powder and the dispersant as described in claim 1 are placed in a container and mixed to obtain a pretreated product; 2) Place the magnetic rod in the stirring device, add the pretreatment material to the stirring device and stir. After completion, wash and collect the material adsorbed on the magnetic rod to complete the enrichment of magnetic materials in the regenerated lithium iron phosphate powder.

7. The method according to claim 6, characterized in that, In step 1), the mass ratio of lithium iron phosphate powder to dispersant is 1:2-2.

5.

8. The method according to claim 6, characterized in that, In step 2), the magnetic rod is a Teflon magnetic rod, and the magnetic induction intensity of the magnetic rod is 5500-6000GS.

9. The method according to claim 6, characterized in that, In step 2), the stirring device is a ball mill.

10. The method according to claim 6, characterized in that, In step 2), the stirring speed is 115-125 rpm and the stirring time is 30 min.